(untitled) (Raparin Journal of Humanities (RJH), 2022)
The United States’ new foreign policy, which includes abandoning America’s Kurdish friends and a new strategy on how the US should execute military interventions, as well as the "America First" ethos, has triggered a humanitarian and military catastrophe for Syrian Kurds. Despite the prevalence of study on American strategy in Syria and towards Syrian Kurds, there is a noticeable lack of comprehensive research explaining and evaluating the growing connections. This paper argues that deciphering these patterns necessitates a deep understanding of regional politics and a thorough engagement with the vast IR research. In this context, it is essential to look at the nature, limitations, and constraints of the Kurdish-US relationship, which is the Kurds’ most powerful ally. For the present study, a theoretical framework is chosen to analyse US foreign policy comprehensively. This is a qualitative research report based on a case study. The case for this paper is the United States’ foreign policy toward Syrian Kurds, as seen through several international theories, particularly realism and liberalism. The suggested study aims to explain why the US overlooked Syrian Kurds at the start of the Syrian crisis, why the US worked with and backed Syrian Kurds or SDF till 2019, and why the US abandoned or deserted the Syrian Kurds after a foreign policy shift. To sum up, scholarly reports show mixed results, with some claiming that the US decision to abandon Syrian Kurds was well-informed. In contrast, others suggest that if the decision is made without caution, it will do more harm than good to America’s long-term ally, who played a critical role in the fight against the Islamic State of Iraq and Syria.